IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY - Ahmad Bashri; Rinie Pratiwi Puspitawati; Muji Sri Prastiwi (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
The development of learning media is absolutely done by teachers in schools. Learning media is a tool or means used to convey messages of learning material from educators to students. The development of learning media is growing rapidly along with technological developments. This acceleration is further spurred by the demands of online learning during the COVID-19 pandemic. One of the appropriate learning media to facilitate the delivery of subject matter is digital augmented reality-based media. Now this media is in line with the implementation of the Society 5.0 era, where this concept is human-centered and technology-based. However, it is necessary to sort out the types of learning materials that are suitable for augmented reality media, namely materials that are difficult to do when social restrictions occur and can still be contextualized through these media. The application of augmented reality-based media is very much needed in educational institutions under the pesantren environment, one of which is SMA Assa'adah under the management of the Pondok Pesantren (Islamic Boarding School) of Qomaruddin, Bungah Gresik. The targets and products to be achieved are: 1) Develop school programs in the development of augmented reality-based learning media for subject matter, 2) Develop student worksheet and evaluation instruments related to augmented reality learning media, and 3) find out partner responses during the implementation of learning media based augmented reality. The method in this activity is divided into three phases. The first phase is the preparation phase. At this stage, the preparation of materials, instruments and examples of assessments that will be used during the implementation of activities through Focus Group Discussion (FGD) between partners and the Unesa team will be carried out. The second phase is the implementation of activities that will be carried out through providing information, modeling, practice by participants to use AR media, and compiling student worksheet. In the third phase, a workshop on the preparation of evaluation instruments was carried out and continued with evaluation and feedback on things that were necessary in implementation activities. The results of the activity show that 1) institutional school partners have prepared plans for developing AR-based learning media for a five-year period, 2) teacher partners have been able to develop student worksheet by utilizing augmented reality-based media; and 3) partners have responded very well to the implementation of augmented reality-based learning media with the Unesa mentoring team. Keywords: Learning media, augmented reality